Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Ditonk Group Bersih Di Kota Tangerang - Nur Hasyim, Ikhwan; Suworo Suworo (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of promotion on customer satisfaction at PT. Ditonk Group Bersih in Tangerang City, to determine the effect of service quality on customer satisfaction at PT. Ditonk Group Bersih in Tangerang City, and to determine the effect of promotion and service quality simultaneously on customer satisfaction at PT. Ditonk Group Bersih in Tangerang City. The method used in this research is quantitative. The sampling technique was carried out using the Slovin formula, resulting in a sample of 100 respondents. Data analysis techniques include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the study show that promotion has a significant effect on customer satisfaction with a coefficient of determination of 36.9%, and the hypothesis test obtained t-count > t-table (7.562 > 1.661). Service quality has a significant effect on customer satisfaction with a coefficient of determination of 24.4%, and the hypothesis test obtained t-count > t-table (5.620 > 1.661). Promotion and service quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 12.663 + 0.467X1 + 0.224X2. The coefficient of determination is 41.4%, while the remaining 58.6% is influenced by other factors. The hypothesis test obtained F-count > F-table (33.884 > 2.36).